Triangular Fuzzy Metric - Mohammad A. Mahmoud Al-Amleh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This paper presents a new method to rank triangular fuzzy numbers as well as a new metric (triangular fuzzy metric) on the set of fuzzy points. This metric can be used in both studying fuzzy topological spaces and decision-making theory.